Psychological and Cultural Factors: Does an Accounting Study Program Matter? - Frista Fio Amanda; Zaky Machmuddah (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2025)
ABSTRACT The phenomenon of declining interest in accounting study programs has become a significant issue in Indonesian higher education. This study aims to analyze the influence of psychological, social, and cultural factors on students decisions to major in accounting at university "Y." The study sample consisted of 113 new students from the class of 2025 selected through accidental sampling. Data analysis used multiple linear regression with IBM SPSS 25. The study results indicate that psychological and cultural factors significantly influence students decisions, while social factors have no significant influence. These findings indicate that personality, interests, and cultural values ​​are key considerations in choosing an accounting study program. The practical implications of this study are highly beneficial for accounting study program managers in designing more effective promotion and admission strategies in the digital era and serve as a reference for further research.